How Lessons Learned from the Early Churches Help Today’s China House Churches Practice Public Theology and Survive Under Authoritarian Rule - Agnes, C. (University of jaffna, 2024)
China’s House Churches have gone through intensive persecution in recent years: church buildings closed by government forces, leaders imprisoned, biblical materials seized, and members under constant threats of imprisonment. Socially, China continues to become more secular in culture. Economically, the country is in a financial downturn with a massive youth unemployment. Politically, a war conflict with Taiwan is looming. For house church Christians in China, the call to live out their faith in public spheres and practice public theology seems impossible and impractical. Yet, examples of Christians in the early church provide encouragement and hope for today’s Christians under authoritarian rule. The similarities between the early churches and today’s house churches in China are striking – cultural rejection, religious intolerance, political oppression, and lack of material resources. Yet, Christians from the early churches strived in number and influence. The mode of evangelism and living out their faith despite oppression provides much insight to today’s Christians. Small gatherings, home evangelism, personal testimony, and lifestyle evangelism are all methods used by early church Christians, which can be of reference to today’s Christians in China. House church Christians in China are already changing their practice from mega-churches in the 1990s to small gatherings of fewer than ten people. This paper analyzes the examples of evangelism through practicing public theology and living out one’s faith in daily living. The lessons from the early church’s history encourage today’s house church Christians and believers under persecution to persevere and remain hopeful. These lessons also provide a paradigm for doing public theology in a state of authoritarian rule. Christians outside of repressive regimes can also learn how to help with the needs of the oppressed brothers and sisters.
Keywords: House churches in china; Public theology in daily living